The Gestapo : The Myth and Reality of Hitler's Secret Police - McDonough, Frank (London Coronet, 2016)
The Gestapo was Hitler's secret police force. Popularly depicted as a central part of an all-powerful 'Big Brother' Nazi totalitarian police state, its primary aim was to hunt down 'the enemies of the people'. Drawing on a detailed examination of previously unpublished Gestapo case files this book relates the fascinating, vivid and disturbing stories of a cross-section of ordinary and extraordinary people who opposed the Nazi regime. It also tells the equally disturbing stories of their friends, neighbours and sometimes even relatives, people drawn into the Gestapo's web of intrigue, either as informers or as staff. The book reveals, too, the cold-blooded and efficient methods of the Gestapo officers. This book will reveal that the Gestapo lacked the manpower and resources to spy on everyone, that it was reliant on tip offs from the general public. Yet this did not mean the Gestapo was a weak or inefficient instrument of Nazi terror. On the contrary, it ruthlessly and efficiently targeted its officers against clearly defined political and racial 'enemies of the people'. The book provides a chilling new doorway into the everyday life of the Third Reich, gives powerful testimony from the victims of Nazi terror, offers a range of fascinating and poignant life stories of those who opposed Hitler's regime unearths new evidence from Gestapo case files and challenges popular myths on the Gestapo.
Include Illustrations and Index.
English Biography.
Keywords: Germany -- Germany. Geheime Staatspolizei -- Police